Hot days and Covid-19: Online survey of nurses and nursing assistants to assess occupational heat stress in Germany during summer 2020 - Yvette Jegodka; Lena Lagally; Hanna Mertes; Katharina Deering; Julia Schoierer; Barbara Buchberger; Stephan Bose-O'Reilly (Elsevier, 2021)
Objectives: Our aim was to identify if working during hot days while wearing Covid-19 related personal protective equipment causes occupational heat stress for nurses and nursing assistants in Germany. Design: Using an online survey, we assessed the impact of hot weather on nurses and nursing assistants working with personal protective equipment. Respondents were recruited by distributing the link to the survey via personal communication, email and various social media channels to nursing staff from hospitals, nursing homes and outpatient care. Results: There were in total 428 participants (18.2% male, 82.5% female), mostly (30.5%) aged between 45 and 55 years. Half of respondents (48.3%) had more than 20 years of experience in nursing. Cardiac, pulmonary, or other pre-existing conditions were reported by 46.2%.Nurses and nursing assistants working in personal protective equipment during hot days were exposed to occupational heat stress. Work was found exhaustive by 96.5% of the participants during those days. 93.0% reported breathing problems and 85.8% reported difficulties with focusing on their work. Many workplaces did not provide adequate heat protection, with distinct differences concerning the amount of prophylactic and heat mitigating measures across institutions. There were significant differences across institutions when it comes to the number of drinks served (p < 0.001), the availability of room thermometers (p < 0.001), the use of mobile cooling devices (p < 0.001) and fans (p < 0.05). Conclusions: Results suggest employers must make more of an effort to provide adequate heat protection for their nursing staff. In order to ensure patient care, there is a need for action; in particular, attention must be paid to the pre-existing health conditions of the nursing staff.